The Common Agricultural Policy and income disparities in Italian agriculture - Pupo D'Andrea, Maria Rosaria; Carillo, Felicetta; Scardera, Alfonso; Henke, Roberto (Italian Review of Agricultural Economics, 2025)
This paper investigates the persistence of territorial disparities in agricultural income across Italian macro-regions, with a particular focus on the role of the Common Agricultural Policy (CAP). Drawing on the Italian Farm Accountancy Data Network (FADN) dataset, this study develops and applies a set of income indicators to examine whether CAP support has contributed to narrowing or widening regional agricultural income gaps at the farm level. The results confirm that despite the redistribution efforts embedded in the CAP, especially through the internal convergence mechanism, the agricultural income gap between North and South Italy has persisted and, in some cases, widened. Regression analyses at the farm level reveal that CAP support, though relatively higher in South Italy, has not sufficiently counterbalanced the lower market-based income. The findings suggest that while the CAP is not designed as a redistributive instrument, it has had a limited impact on fostering income convergence in agriculture. These results underscore the need for a more integrated and place-based policy mix to promote balanced development and to foster fair development in rural areas.